2020
DOI: 10.47605/tapro.v9i1.216
|View full text |Cite
|
Sign up to set email alerts
|

REDISCOVERY OF MODIGLIANI’S NOSE-HORNED LIZARD, Harpesaurus modiglianii VINCIGUERRA, 1933 (REPTILIA : AGAMIDAE) AFTER 129 YEARS WITHOUT ANY OBSERVATION

Abstract: The Modigliani’s nose-horned lizard, Harpesaurus modiglianii Vinciguerra, 1933, is one of the rarest lizards in the world, known only from its single type specimen collected in 1891, from North Sumatra, Indonesia. During explorations of the forests surrounding Lake Toba and its caldera, we discovered a population of H. modiglianii at an elevation of 1,675 m a.s.l., and provide the first data on its habitat. We here re-describe the species based on an examination of its type and new material, and provide an Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…This interpretation likely explains apparent rarity of some Harpesaurus. Harpesaurus modiglianii Vinciguerra (1933) was known only from the holotype collected in 1891 until Putra et al (2020) discovered a population of these rare lizards near Lake Toba, North Sumatra. Putra et al (2020) found their new specimen 4 m aboveground on a horizontal branch, sufficiently high in the forest that it might have been overlooked by most herpetologists.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation likely explains apparent rarity of some Harpesaurus. Harpesaurus modiglianii Vinciguerra (1933) was known only from the holotype collected in 1891 until Putra et al (2020) discovered a population of these rare lizards near Lake Toba, North Sumatra. Putra et al (2020) found their new specimen 4 m aboveground on a horizontal branch, sufficiently high in the forest that it might have been overlooked by most herpetologists.…”
Section: Discussionmentioning
confidence: 99%
“…However, Sumatra’s cloud forest biodiversity has remained largely unexplored and the pressures that have driven the development of that diversity are not yet fully understood ( O’Connell et al 2018 ). Reptilian diversity is no exception in this regard despite the fact that Sumatra is known to harbor some of the most evolutionarily unique lineages of reptiles, including enigmatic species like the Modigliani’s nose-horned lizard which was recently rediscovered ( Putra et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%